The importance of dietary magnesium sulphate for prophylaxis of parturient paresis in cow with high milk production - M. Ali Bostancı; Mahmut Ok (Eurasian Journal of Veterinary Sciences)
The aim ol this study is to search for changing of acid- base balance, Ca++, Mg++ and P+ levels, when MgS04 is added to the ration for last penod of pregnancy in cows. Thus, understanding of importance of this material for prophylaxis in parturient paresis. As a material, 18 cows which will have given a birth within 20 and 30 days, have been used. The animals are divided 3 groups (each group include 6 animals). First group, the cows has been used as a control, 11, group animals which will have given a birth within 20 days, has been used. These animals were led with 126 gr MgS04 which was added in the ration. III. Group animals which will have given a birth within 1 month . These animals are fed with 126 gr MgSO4 which was added in the ration. Compare with same samples times have been evaluated of each groups, there is significantly decrease lor HC03- (p<0.05) levels between group I and III for 4th and 6th sampled. There is statistically decrease for BE levels( p<0,05. p<0.005) in the group I, grup II and group III for plasma samples which are collected 3rd, 4rd, 5th, 6th and after to given a birth, There is significantly increase for plasma ICa++ level (p<0.05, p<0.005) between group 1 and group II considered for collection of 5th and 6th sampled. Similar result were taken between group I and III (p<0.05, p<0.005) considered for collection of 3rd, 4rd, 5th and 6th sampled period. Total serum Ca++ levels (p<0.05, p<0.005) also show statistically differences between group I and group II for 5th, 6th and after to given a birth sampled period, comparasion study show that there-is differences between group I and III collection of 4rd, 5th,6th and after to given a birth sampled period lime. In case of this result, there is significatly decrease for P+ (p<0.05)levels between group I and III for 5th and 6th sampled during the study. But also there is significatly decrease for K+ (p<0.05)levels between group 1 and III for 6th and after to given a birth sampled period time. Magnesium sulphate which is added lo the ration last period of cow pregnancy period, is help to stimulate increasing of plasma TCa++ and ICa++ levels statisticaly significantly. This result is indicate that parturient paresis could be prevented by adding magnesium sulphate in the ration within the last period of cow pregnancy period.